Enhancing the Ability of Escherichia coli to Synthesise L-Isoleucine Using λ-Red Recombinant Technology Combined with Complex Mutagenesis - Jipeng WANG; Tengteng ZHU; Lu LIU; Cheng MA; Xiaobo WEI; Huiyan LIU; Haitian FANG (Shipin gongye ke-ji, 2025)
To improve the synthetic ability of E. coli L-isoleucine by combining λ-Red recombination with complex mutagenesis. Firstly, taking E. coli NXA as the original strain, λ-Red homologous recombination was used to knock out the coding gene brnQ of branched chain amino acid transport protein to obtain mutant strain E. coli NXA1. Secondly, E. coli NXA1 was subjected to multiple rounds of complex mutagenesis with atmospheric room temperature plasma (ARTP), ultraviolet (UV), and nitrosoguanidine (NTG), which was screened to obtain the mutant strain E. coli NXA2 with α-AB being structural analogue. The fermentation results showed that L-isoleucine titer of E. coli NXA1 was 2.76 g/L, which was 33.98% higher than E. coli NXA after fermentation for 40 hours at 37 ℃ and 200 r/min. The L-isoleucine titer of E. coli NXA2 was 3.22 g/L, which was 16.67% higher than E. coli NXA1 and 56.31% higher than E. coli NXA. After 20 continuous passages of E. coli NXA2, the good genetic stability could be reflected. The combination of λ-Red recombination and complex mutagenesis has a significant effect on improving the synthetic ability of E. coli L-isoleucine, laying a theoretical basis for the breeding of L-isoleucine high-producing strains.